The Politics of Borders in the Emergence of Modern Swedish Craft. (2nd January 2019) - Keshavarz, Mahmoud; Zetterlund, Christina
Abstract: Nation states have been imagined and constructed by defining certain identities and practices. Among cultural and economic practices bound to material culture, craft has played a significant role in the processes of imagining communities and consequently nationalities in modern times. These imaginations were produced and sustained by various discursive and materialized borders that were based on simultaneous practices of inclusion and exclusion, targeting certain bodies within the formation of a nation state. In this article, we discuss instances of such bordering in Sweden, by looking at specific state documents of controlling the movement and residence of those who were seen as suspicious and potentially threatening. Among these individuals were craftspeople with religious and/or ethnic backgrounds different than the imagined modern Swedish subjects. They were often represented as a threat to the economic, social, and cultural prosperity of the Swedish nation state. These individuals and groups, and their craft practices, were variously appropriated, erased, included, and excluded by the nation state. This article argues that an understanding of modern Swedish craft is impossible without recognizing the crafts that were excluded from its emergence, articulation, and sustainment over the last hundred years. This is to argue that an understanding of the politics of craft requires recognition of the borders that regulate how—and by whom—craft can be practiced.